Obstacles and Challenges in Publishing Faculty Members' Scientific Books in Shahid Beheshti University of Medical Science - Zahra Alaie; Soleiman Ahmadi; Mohammad-Reza Sohrabi (Shahid Beheshti University of Medical Sciences, 2019)
Background and Objective: Considering the importance of scientific productions on national and international levels, this study aimed to assess the challenges and obstacles of publishing national books by faculty members of Shahid Beheshti University of medical Sciences. Materials and Methods: This qualitative research was conducted with participation of 13 faculty members who had long experiences in education and also publishing scientific books and were chosen by targeted sampling method.  They were interviewed after providing informed consent. The duration of each semi-structured interview was 30-60 minutes; all of them were recorded. The transcripts were written word by word and analyzed using qualitative content analysis. Results: From 13 interviews, 510 primary codes were extracted and finally six themes of frequency and variety of policies, unclear outcomes, article-based researches, supportive approaches, lack of experienced researchers and lack of effective scientific networks were defined. In addition, 25 sub-themes were categorized under the themes. Conclusion: The study showed that despite the development of research and the related facilities, there are still challenges for publishing the books. Interventions in the fields of emotional, rules and regulations and financial incentives could be suggested for improvement. DOI: http://doi.org/10.22037/ch.v6i3.25588